Feasibility of Worksheet Based on PBL to Improve Students Critical Thinking Skills on Acid-Base Material - Putri, Alifiyah; Yonata, Bertha (Universitas Syiah Kuala, 2024)
Critical thinking skills are important for students to improve in facing the challenges of the 21st century. One of the way to improve critical thingking skills is by using relevant learning media, namely worksheet based on problem based learning (PBL) model. The purpose of this research is to obtain a worksheet based on PBL to improve students' critical thinking skills on acid-base material. The feasibility of the worksheet is reviewed from the aspects of validity, practicality and effectiveness. This type of research is research and development (RD) with Thiagarajans 4D development model. In this research was only carried out to the development stage with limited trials on 15 students of SMAN 7 Surabaya. The results showed that the worksheet was declared valid in terms of the mode score of content validity of 5 with a very valid category, and construct validity of 4 with a valid category. The practicality of worksheet is reviewed from the results of the student response questionnaire, namely that students respond positively to the use of worksheet based on PBL to improve critical thinking skills and is supported by the results of observing that students' relevant activities are greater than irrelevant activities. The effectiveness of the LKPD is reviewed from the results of the critical thinking skills posttest in the aspects interpretation 92%, explanation 72%, analysis 93%, and inference 83%. Meanwhile, for the N-Gain results from the pretest and posttest of critical thinking skill, obtain a score of 0.3 with moderate and high categories. And supported by the results of knowledge tests where all students have achieved individual mastery with a score of 75. Based on these results, it can be concluded that LKPD based on PBL to improve students' critical thinking skills on acid and base material is feasible to use